2021
DOI: 10.1128/iai.00023-21
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pneumococcal Genetic Adaptations Support Bacterial Growth and Inflammation during Coinfection with Influenza

Abstract: Streptococcus pneumoniae (pneumococcus) is one of the primary bacterial pathogens that complicates influenza virus infections. These bacterial coinfections increase influenza-associated morbidity and mortality through a number of immunological and viral-mediated mechanisms, but the specific bacterial genes that contribute to post-influenza pathogenicity are not known. Here, we used genome-wide transposon mutagenesis (Tn-Seq) to reveal bacterial genes that confer improved fitness in influenza-infected hosts. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Although the pathogenicity was increased during the coinfections at 5 d and 7 d pvi, there seemed to be little contribution from SARS-CoV-2, where the burden and distribution did not change within the first 24 h pbi (Figure 2) despite reduced CD8 + T cells in some groups (Figure 3G). In IAVpneumococcal coinfections, invading bacteria result in robustly increased viral loads 55,68,82,[131][132][133] regardless of timing 55 and viral dissemination in the lung is increased by 30-50% 55 . Our prior work 55 suggests this is due to a combination of direct viral-bacterial interactions 97 that lead to viral access to new areas of the lung in addition to increased virus production rates 68 that may be mediated by alterations to the antiviral IFN response 98 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenicity was increased during the coinfections at 5 d and 7 d pvi, there seemed to be little contribution from SARS-CoV-2, where the burden and distribution did not change within the first 24 h pbi (Figure 2) despite reduced CD8 + T cells in some groups (Figure 3G). In IAVpneumococcal coinfections, invading bacteria result in robustly increased viral loads 55,68,82,[131][132][133] regardless of timing 55 and viral dissemination in the lung is increased by 30-50% 55 . Our prior work 55 suggests this is due to a combination of direct viral-bacterial interactions 97 that lead to viral access to new areas of the lung in addition to increased virus production rates 68 that may be mediated by alterations to the antiviral IFN response 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Following bacterial establishment, dysfunction of neutrophils [78][79][80][81] , which may be in part facilitated by bacterial metabolic interactions 82 and type I IFNs 71,82,83 , and additional depletion of AMΦ 55 contribute to bacterial growth and coinfection pathogenesis Reviewed in [39][40][41]45,84,85 . Currently, the effect of SARS-CoV-2 infection on AMΦs remains somewhat unclear, although human, murine, and in vitro data indicate that AMΦs become productively infected with SARS-CoV-2, leading to altered cytokine production and responsiveness [86][87][88][89] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that neutrophil dysfunction contributes to pathogenicity of IAV-pneumococcal coinfection, and this seems to be mediated by bacterial metabolism ( 82 ) and type I IFNs ( 71 , 83 , 127 ). However, unlike IAV-pneumococcal coinfections, type I IFNs were unchanged after SARS-CoV-2-pneumococcal coinfection ( Figure S5 ) and neutrophil infiltration was only observed in coinfection at 7 d pvi ( Figure 3A ), suggesting that there may be different mechanisms underlying the enhanced pathogenicity of SARS-CoV-2 pneumococcal coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive increase in susceptibility to bacterial coinfection during influenza is largely due to the depletion and/or dysfunction of resident alveolar macrophages (AMΦ) during IAV infection, which is dynamic throughout the infection ( 55 , 67 ) and maximal at 7 d pvi ( 55 , 67 69 ). Following bacterial establishment, dysfunction of neutrophils ( 78 – 81 ), which may be in part facilitated by bacterial metabolic interactions ( 82 ) and type I IFNs ( 71 , 82 , 83 ), and additional depletion of AMΦ ( 55 ) contribute to bacterial growth and coinfection pathogenesis [Reviewed in ( 39 41 , 45 , 84 , 85 )]. Currently, the effect of SARS-CoV-2 infection on AMΦs remains somewhat unclear, although human, murine, and in vitro data indicate that AMΦs become productively infected with SARS-CoV-2, leading to altered cytokine production and responsiveness ( 86 89 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation